J. Laurence Laughlin and the Quantity Theory of Money - Girton, Lance; Roper, Don (Journal of Political Economy, 1978)
In this paper the issues raised in the turn-of-the-century American debate over the quantity theory of money are examined. J. Laurence Laughlin of Chicago,the leading antiquantity theorist, provoked the controversy with theoretical and empirical criticisms of the quantity theory, while Irving Fisher emerged as the chief defender of the monetary orthodoxy. Laughlin argued that issues of convertible paper money would not raise prices or the money supply but would instead lead to losses of monetary gold. His position was regarded as incompatible with the classical neutrality-of-money theorem. To identify the fundamental sources of disagreement between Laughlin and the quantity theorists, the neutrality-of-money proposition is decomposed into two components the neutrality proposition per se and the assumed causal role of money.